2008
DOI: 10.1073/pnas.0710581105
|View full text |Cite
|
Sign up to set email alerts
|

Mapping H5N1 highly pathogenic avian influenza risk in Southeast Asia

Abstract: The highly pathogenic avian influenza (HPAI) H5N1 virus that emerged in southern China in the mid-1990s has in recent years evolved into the first HPAI panzootic. In many countries where the virus was detected, the virus was successfully controlled, whereas other countries face periodic reoccurrence despite significant control efforts. A central question is to understand the factors favoring the continuing reoccurrence of the virus. The abundance of domestic ducks, in particular free-grazing ducks feeding in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
317
9
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(353 citation statements)
references
References 30 publications
26
317
9
1
Order By: Relevance
“…In particular, the present study not only showed that neighbourhood landscapes with predominant rice production were associated with higher seroprevalence level, which is consistent with previous studies on eco-epidemiology of HPAI H5N1 in Southeast Asia (Gilbert et al, 2008), but was also the first to demonstrate this effect for LPAI in a non-Asian setting. It has been suggested that rice paddy fields may favour HPAI H5N1 persistence because they constitute an interface between wild birds feeding there, and domestic poultry.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In particular, the present study not only showed that neighbourhood landscapes with predominant rice production were associated with higher seroprevalence level, which is consistent with previous studies on eco-epidemiology of HPAI H5N1 in Southeast Asia (Gilbert et al, 2008), but was also the first to demonstrate this effect for LPAI in a non-Asian setting. It has been suggested that rice paddy fields may favour HPAI H5N1 persistence because they constitute an interface between wild birds feeding there, and domestic poultry.…”
Section: Discussionsupporting
confidence: 80%
“…The fre-quent flooding of rice fields would also allow a greater viral persistence in this environment compared to dry soils (Van Boeckel et al, 2012). Reports from Thailand, Vietnam and Indonesia (Gilbert et al, 2008;Loth et al, 2011) found that HPAI H5N1 outbreaks occurred mainly in areas where rice is cultivated through an intensive, multiple crop system. The authors suggested that this may be related to the fact that the highest numbers of free-grazing ducks are raised in these areas, where the irrigation network is the densest and flooding the most frequent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research 30 A study is published describing the epidemiological association between the presence of H5N1 virus and duck populations, human populations, and rice production in Viet Nam and Thailand.…”
Section: Mar 2008mentioning
confidence: 99%
“…11,12,23,38 In contrast to chickens, in which infection is usually fatal, clinical signs in domestic ducks infected with the H5N1 HPAI virus greatly vary, ranging from asymptomatic to a fatal infection. 29,30,40,54 The main epidemiologic problem is that asymptomatically infected ducks can shed the virus for a particular period.…”
mentioning
confidence: 99%